2004
DOI: 10.4028/www.scientific.net/kem.274-276.1053
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on the Inhomogeneous Microstructure in Crack Healing Area

Abstract: Three hypo-eutectoid steels were chosen to study the inhomogenoues microstructure in crack healing area. Internal cracks were made in 20, 20MnMo and 45 steel samples. The precracks in 20 and 20MnMo steel can mostly be healed under the conditions of hot plastic deformation in which the reduction of hot pressing were 35.6% and 44.9% respectively, and the healing area is a ferrite band. The process of crack healing in crack tips in 45 steel could be finished in a very short time during upsetting, but there exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It was suggested that the thermal or mechanical treatment provides the driving force to minimise the surface energy resulting in the crack healing [6]. The healing of internal pre-cracks obtained using plate impact technology was studied in a vacuum at an elevated temperature [7,8], and the inhomogeneous microstructure in crack healing area was analysed [9]. It has been shown that the healing of fine cracks (100 nm) begins immediately after heating then proceeds according to the vacancy diffusion mechanism in the surface layer about 10 μm thick [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the thermal or mechanical treatment provides the driving force to minimise the surface energy resulting in the crack healing [6]. The healing of internal pre-cracks obtained using plate impact technology was studied in a vacuum at an elevated temperature [7,8], and the inhomogeneous microstructure in crack healing area was analysed [9]. It has been shown that the healing of fine cracks (100 nm) begins immediately after heating then proceeds according to the vacancy diffusion mechanism in the surface layer about 10 μm thick [10].…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [4] investigated the crack healing in 20MnMo steel. Wei et al [5] studied the crack healing behaviour in plain carbon steel at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Real internal pre-cracks were obtained in pure copper and steel using plate impact technology [8]. The healing of these cracks was studied in a vacuum at an elevated temperature [9][10][11], and the inhomogeneous microstructure in crack healing area was also analysed [12]. It has been shown that the healing of fine cracks (100 nm) begins immediately after heating then proceeds according to the vacancy diffusion mechanism in the surface layer about 10 μm thick [13].…”
Section: Introductionmentioning
confidence: 99%